«The Mechanism of Mendelian Heredity» (The 100th anniversary of the first publication of the book by the group of T.H. Morgan) - E. B. Muzrukova (Вавиловский журнал генетики и селекции)
The article is dedicated to the 100th anniversary of the first Morgan’s book, «The Mechanism of Mendelian Heredity» in 1915. The book presented the program of Morgan’s genetic research. The necessity of this article stems from the fact that T.H. Morgan is a unique historical figure, which personifies the development of a new branch of biology, genetics, in the first decades of the 20th century. The works by Morgan and his disciples illustrate the relationships between genetics and other fields of biology. Historical analysis of the monograph sheds light to key points in the formation of genetics as a science in the early 20th century. Moreover, the activities of Morgan’s group is a prominent example of a scientific school, the first in genetics.It is owing to that school, America gained the leadership in genetic research from Europe. Cytological analysis of chromosomal rearrangements and study of mutations played the key role in the formation of the chromosome theory of inheritance. By studying mutations in Drosophila, Morgan obtained an experimental proof of linkage of individual genes in a chromosome. Study of deviations in the linkage provided grounds for the discovery of crossover, which was a great stride forward. Construction of chromosome maps and investigation of chromosome rearrangements stem from Morgan’s school. When reading his Nobel lecture in 1934, Morgan presented not only the results of his group but also a long-range program of genetics development.